Blacksmith’s Dystonia Is Another Task-Specific Dystonia: From Past to Present - Kim, Min Seung; Park, Don Gueu; Yoon, Jung Han (Journal of movement disorders, 2022)
Writer’s cramp and musician’s dystonia are the most common forms of TSD, and various types of TSD associated with patient occupations have been reported. Several occupations have disappeared over time and are no longer present in the modern era. Here, we report a patient with proximal arm dystonia triggered by using a hammer associated with his unique and traditional occupation, a blacksmith. KCI Citation Count: 0